A single oral glucose load decreases arterial plasma [K+] during exercise and recovery. Issue 11 (10th June 2021) - Steward, Collene H.; Smith, Robert; Stepto, Nigel K.; Brown, Malcolm; Ng, Irene; McKenna, Michael J.
Abstract: Aim: We investigated whether acute carbohydrate ingestion reduced arterial potassium concentration ([K + ]) during and after intense exercise and delayed fatigue. Methods: In a randomized, double‐blind crossover design, eight males ingested 300 ml water containing 75 g glucose (CHO) or placebo (CON); rested for 60 min, then performed high‐intensity intermittent cycling (HIIC) at 130% V ˙ O 2peak, comprising three 45‐s exercise bouts (EB), then a fourth EB until fatigue. Radial arterial (a) and antecubital venous (v) blood was sampled at rest, before, during and after HIIC and analyzed for plasma ions and metabolites, with forearm arteriovenous differences (a‐v diff) calculated to assess inactive forearm muscle effects. Results: Glucose ingestion elevated [glucose]a and [insulin]a above CON ( p = .001), being, respectively, 2‐ and 5‐fold higher during CHO at 60 min after ingestion ( p = .001). Plasma [K + ]a rose during and declined following each exercise bout in HIIC ( p = .001), falling below baseline at 5 min post‐exercise ( p = .007). Both [K + ]a and [K + ]v were lower during CHO ( p = .036, p = .001, respectively, treatment main effect). The [K + ]a‐v diff across the forearm widened during exercise ( p = .001), returned to baseline during recovery, and was greater in CHO than CON during EB1, EB2 ( p = .001) and EB3 ( p = .005). Time to fatigue did not differ between trials. Conclusion: Acute oral glucose ingestion, as used in a glucose tolerance test, induced a small, systemic K + ‐lowering effect before, during, and after HIIC, that was detectable in both arterial and venous plasma. This likely reflects insulin‐mediated, increased Na +, K + ‐ATPase induced K + uptake into non‐contracting muscles. However, glucose ingestion did not delay fatigue. Abstract : Acute glucose intake substantially elevated insulin, with a systemic K + ‐lowering effect evident in arterial and antecubital venous plasma before, during, and post‐exercise. An increased arterio‐venous K + difference across the relatively inactive forearm musculature with glucose ingestion was consistent with increased K + uptake in non‐active muscle; this was likely mediated via insulin‐induced activation of sodium‐potassium ATPase.